A textbook of basic electronics - Raychaudhuri, Barun (Chhaya prakashani, 2009)
A textbook of basic electronics / Raychaudhuri, Barun. -- Kolkata: Chhaya prakashani, 2009 621.382 R888 No. of Copies : 2